x2-x=56

Move 56 to the left side of the equation by subtracting it from both sides.

x2-x-56=0

Consider the form x2+bx+c. Find a pair of integers whose product is c and whose sum is b. In this case, whose product is -56 and whose sum is -1.

-8,7

Write the factored form using these integers.

(x-8)(x+7)=0

(x-8)(x+7)=0

If any individual factor on the left side of the equation is equal to 0, the entire expression will be equal to 0.

x-8=0

x+7=0

Set the first factor equal to 0.

x-8=0

Add 8 to both sides of the equation.

x=8

x=8

Set the next factor equal to 0.

x+7=0

Subtract 7 from both sides of the equation.

x=-7

x=-7

The final solution is all the values that make (x-8)(x+7)=0 true.

x=8,-7

Solve Using the Square Root Property x^2-x=56